How to deal with radio astronomy interference - Umar, Roslan; Hazmin, Sabri Nor; Abdin, Zamri Zainal; Ibrahim, Zainol Abidin (2015)
Radio sources are very weak, as they can travel through large distances. Radio sources also have photons with low energies compared to others electromagnetic waves (EM). Microwave photons have a little more energy than radio waves, infrared photons have still more, then visible, ultraviolet, X-rays, and the most energetic electromagnetic wave is gamma-rays. Radio astronomy studies are restricted due to radio frequency interference (RFI) produced by people. If this disturbance is not minimized, it poses critical problems for astrophysical studies. The purpose of this paper is to profile RFI maps in Peninsular Malaysia with a minimum mapping technique for RFI interference. Decision-making processes using GIS (Geographical Information System) for the selection requires gathering information for a variety of parameters. These factors affecting the selection process are also taken into account. In this study, various factors or parameters are involved, such as the availability of telecommunications transmission (including radio and television), rainfall, water lines and human activity. This mapping step must be followed by RFI site testing in order to identify areas of low RFI. This study will benefit radio astronomy research, especially regarding the RFI profile.